PERLINDUNGAN HAK PENGEMUDI DISABILITAS (TUNA DAKSA) DALAM PERJANJIAN KEMITRAAN ANTARA GO-JEK DAN MITRA KERJA PENGEMUDI DI PEKANBARU - Tedy Desprianda; Emilda Firdaus; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Article 1 paragraph (3) of the Constitution 1945 states that Indonesia is a legal state. Thus the country guarantees the legal rights of its citizens by providing legal protection and legal protection will be the right for every citizen. Legal protections are provided to everyone including disabilities. People know the term disability or disability as someone who bears defects. Society mostly implies people with disabilities as individuals who lose members or body structures such as foot/hand, paralyzed, blind, deaf, etc. Everyone has the potential to become a disability. A person can be a disability not only because of the abnormalities in the womb, but disabilities can also occur in children, adolescents, adults, and older people. Anyone can get an accident on the highway, a work accident, or a victim of natural disasters. This can cause a person to become a disability. In addition, disability protection can also be interpreted as an effort to create an environment and public facilities that are accessibility for the similarity of opportunities for people with disabilities to live independently and in society. That means they also have the right to be independent in working like normal people anyway.Partnerships are efforts involving various sectors, community groups, government agencies and non-Governments to cooperate to achieve a common goal based on their respective principle and role agreements. It means that the essence of the partnership is